2022
DOI: 10.2147/ppa.s345906
|View full text |Cite
|
Sign up to set email alerts
|

Preferences and Priorities for Relapsed Multiple Myeloma Treatments Among Patients and Caregivers in the United States

Abstract: Introduction/Background This study aimed to describe patient and caregiver preferences for treatments of relapsed or refractory multiple myeloma (MM). Materials and Methods A survey including discrete-choice experiment (DCE) and best-worst scaling (BWS) exercises was conducted among US patients with relapsed or refractory MM and their caregivers. The DCE included six attributes with varying levels including progression-free survival (PFS), toxicity, and mode and frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…About half of the studies ( n = 16, 47%) used in-depth or semi-structured interviews. Only two studies (6%) involved patient focus groups in developing the attributes [ 41 , 52 ]. We found that the attribute identification process was not sufficiently reported, which may have impacted the transparency and validity of some DCEs.…”
Section: Resultsmentioning
confidence: 99%
“…About half of the studies ( n = 16, 47%) used in-depth or semi-structured interviews. Only two studies (6%) involved patient focus groups in developing the attributes [ 41 , 52 ]. We found that the attribute identification process was not sufficiently reported, which may have impacted the transparency and validity of some DCEs.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of newer treatment options has facilitated personalized management strategies to optimize outcomes but also has led to an increasingly complex treatment pathway (11,12). As a result, physicians need to balance efficacy and safety with assessment of patients' needs and related considerations, such as those associated with treatment administration procedures, when considering therapeutic options (13).…”
Section: Introductionmentioning
confidence: 99%